2020
DOI: 10.2174/1389202921666200106111813
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Machine Learning in miRNA Discovery and Target Prediction

Abstract: MicroRNA (miRNA) is a small non-coding molecule that is involved in gene regulation and RNA silencing by complementary on their targets. Experimental methods for target prediction can be time-consuming and expensive. Thus, the application of the computational approach is implicated to enlighten these complications with experimental studies. However, there is still a need for an optimized approach in miRNA biology. Therefore, machine learning (ML) would initiate a new era of research in miRNA biology towards po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In recent years, miRNAs have been identified in some plants species through cloning and computational approaches (Saliminejad et al, 2019;Smoczynska et al, 2019), and it has also been shown that miRNAs may be predicted using modern machine learning approaches (Parveen et al, 2019;Esposito et al, 2020). Recent reports have identified hundreds of miRNAs in several species, including Fragaria vesca (Han et al, 2019), cardamom (Anjali et al, 2019), sweet cherry (Wang et al, 2019), and Brazilian pine (Galdino et al, 2019) through highthroughput sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, miRNAs have been identified in some plants species through cloning and computational approaches (Saliminejad et al, 2019;Smoczynska et al, 2019), and it has also been shown that miRNAs may be predicted using modern machine learning approaches (Parveen et al, 2019;Esposito et al, 2020). Recent reports have identified hundreds of miRNAs in several species, including Fragaria vesca (Han et al, 2019), cardamom (Anjali et al, 2019), sweet cherry (Wang et al, 2019), and Brazilian pine (Galdino et al, 2019) through highthroughput sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, ML is not programmed to necessitate stringent seed matches in the 3′-UTRs, but it learns by provided examples with biological relevance, so it also allows identifying non-canonical binding sites, including those within the coding regions. On the other hand, ML learns exclusively from the provided examples and consequently it is only able to find results similar to those examples [ 35 ].…”
Section: Mirna Target Predictionmentioning
confidence: 99%
“…Conversely, if the negative and the positive datasets are very similar to each other, the ML approach will not be able to distinguish between them. Moreover, an excess of positive or negative dataset can cause underfitting or overfitting models, respectively [ 35 ]. Finally, the choice of the validation set is critical for ML: to verify its performance, a model should be assessed on a test dataset that is completely different from the dataset used for the training step (training dataset).…”
Section: Mirna Target Predictionmentioning
confidence: 99%
“…Clinical diagnostics, for example, in ophthalmology, can also be supported significantly by methods of advanced data science [ 4 , 5 ]. In addition to the application of ML in diagnostics, there are also promising approaches in such different fields as robotic-assisted surgery [ 6 ], human genomics [ 7 , 8 ] or prevention [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%